SPROUTING BEHAVIOR OF AEROPONIC MINITUBERS OF DIFFERENT VARIETIES - Devi, Sugani (Potato Journal, 2019)
This experiment was performed to investigate the effect of environmental conditions (controlled and natural indoor environment) and harvesting period on sprouting behavior of aeroponic minitubers of seven potato varieties. Data was collected on weight loss percentage, sprouting percentage and emergence percentages for all varieties and treatments. The weight loss percentage in open environment was 20.82 percent which was 203.06 percent higher than controlled environment (6.87%). Highest weight loss was observed in Kufri Badshah (21.58%) followed by Kufri Pukhraj (16.09%) whereas; minimum weight loss was recorded in Kufri Himalini (7.94%). On the other hand, sprouting and emergence percentages were significantly high under controlled temperature conditions as compared to natural indoor conditions.After 30 days of keeping for sprouting in different environments highest sprouting percent was recorded in variety Kufri Himalini (90.93%) followed by Kufri Chipsona-1 (86.67%). Minitubers harvested in the month of February recorded higher sprouting percent (98.84%) as compared to March (84.46%) and April (65.16%) harvested mini-tubers.